Novel and simple route to fabricate fully biocompatible plasmonic mushroom arrays adhered on silk biopolymer. Issue 2 (19th November 2014) - Park, Joonhan; Choi, Yunkyoung; Lee, Myungjae; Jeon, Heonsu; Kim, Sunghwan
Abstract : A fully biocompatible plasmonic quasi-3D nanostructure is demonstrated by a simple and reliable fabrication method using strong adhesion between gold and silk fibroin. Abstract : A fully biocompatible plasmonic quasi-3D nanostructure is demonstrated by a simple and reliable fabrication method using strong adhesion between gold and silk fibroin. The quasi-3D nature gives rise to complex photonic responses in reflectance that are prospectively useful in bio/chemical sensing applications. Laser interference lithography is utilized to fabricate large-area plasmonic nanostructures.